KULTURA I ROZWÓJ JAKO PODSTAWOWE KATEGORIE ODNIESIENIA W TWORZĄCYM SIĘ PRAWIE LUDÓW TUBYLCZYCH - Rudnicki, Zbigniew B. (Zeszyty Prawnicze, 2016)
CULTURE AND DEVELOPMENT AS THE BASIC CATEGORIESOF REFERENCE IN THE EMERGING LAW OF INDIGENOUS PEOPLES Summary In contemporary international relations indigenous peoples constitute particular ethnic communities waiting for a long time for the regulation of their status as subjects of international law. Paradoxically, decolonisation, which helped many colonial societies gain national rights, has not only left the issue of indigenous peoples in countries formerly colonised by the White Man unresolved but has also complicated their status. In practice former colonies such as the United States, Canada, Australia or New Zealand have not regulated the legal status of indigenous peoples, relegating them politically and economically to the margins of society. The rights of indigenous peoples as minority groups living in the former Soviet Union, who are not at all colonial peoples officially, have not been defined either. The category of indigenous peoples now extends to many ethnic groups living in nation-states, who are culturally and linguistically distinct with respect to the dominant segments of the national society. However, assigning the attributes of indigenous peoples to them in the strict sense of the term is questionable and is not dealt with in this article. This article traces the process which leads to indigenous peoples acquiring the status of a fully-fledged subject of international law. It describes attempts that have been made to interpret the rights of indigenous peoples on the grounds of the universal instruments of international law. The principal documents are the Universal Declaration of Human Rights (1948), the Declaration on the Granting of Independence to Colonial Countries and Peoples (1960), the International Convention on the Elimination of All Forms of Racial Discrimination (1966), the United Nations International Covenant on Civil and Political Rights (1966), and finally the Declaration on Principles of International Law Concerning Friendly Relations and Cooperation Among States in Accordance with the Charter of the United Nations (1992). Despite the progress made in granting indigenous peoples their rights with the adoption of the UN Declaration on Indigenous Rights (2007), it is still difficult to talk of full success, i.e. the recognition of the international identity and rights of indigenous peoples on a par with other sovereign nations.